A Hybrid Energy Harvester Based on Piezoelectric and Electromagnetic mechanisms. Issue 1 (1st February 2023) - Shen, Fan; Zhao, Li; Zhang, Qin; Xin, Chuanfu; Gong, Ying; Peng, Yan; Li, Zhongjie
Abstract: This paper presents a hybridization energy harvester (HEH) based on a two degrees-of-freedom (2-DOF) cantilever beam, which combines the electromagnetic effect with the piezoelectric effect. Finite element simulations and some experiments were used to investigate the output of the HEH. For the electromagnetic energy harvester (EMEH), we used an alternating-arranged magnet array to get high electromotive forces. The frequency sweep experiment showed that the resonance frequency of the cantilever beam was about 26.7 Hz which is close to the simulation value, 28.7 Hz. With the increase of excitation acceleration, both piezoelectric and electromagnetic open-circuit voltages increased. The impedance matching experiments of the EMEH and piezoelectric energy harvester (PEH) displayed that the best matching resistors are 35 Ω and 8×10 5 Ω respectively. In capacitor charging experiments, the maximum voltage of the capacitor (220μF) increased from 0.95 V to 1.63 V by paralleling the EMEH and the PEH. But when the EMEH and the PEH were connected in series, the maximum voltage of the capacitor (220μF) was 4.4 V. Therefore, it is clear that the proposed hybridization energy harvester balances the weakness of electromagnetic and piezoelectric harvesters. Besides, it can also make higher output performance.